Development of Tat-Conjugated Dendrimer for Transdermal DNA Vaccine Delivery - Azadeh Bahadoran; Hassan Moeini; Mohd Hair Bejo; Mohd Zobir Hussein; Abdul Rahman Omar (Frontiers Media S.A., 2016)
PURPOSE: In order to enhance cellular uptake and to facilitate transdermal delivery of DNA vaccine, polyamidoamine (PAMAM) dendrimers conjugated with HIV transactivator of transcription (TAT) was developed. METHODS: First, the plasmid DNA (pIRES-H5/GFP) nanoparticle was formulated using PAMAM dendrimer and TAT peptide and then characterized for surface charge, particle size, DNA encapsulation and protection of the pIRES-H5/GFP DNA plasmid to enzymatic digestion. Subsequently, the potency of the TAT-conjugated dendrimer for gene delivery was evaluated through in vitro transfection into Vero cells followed by gene expression analysis including western blotting, fluorescent microscopy and PCR. The effect of the TAT peptide on cellular uptake of DNA vaccine was studied by qRT-PCR and flow cytometry. Finally, the ability of TAT-conjugated PAMAM dendrimer for transdermal delivery of the DNA plasmid was assessed through artificial membranes followed by qRT-PCR and flow cytometry. RESULTS: TAT-conjugated PAMAM dendrimer showed the ability to form a compact and nanometre-sized polyplexes with the plasmid DNA, having the size range of 105 to 115 nm and a positive charge of +42 to +45 mV over the N/P ratio of 6:1(+/-).  In vitro transfection analysis into Vero cells confirms the high potency of TAT-conjugated PAMAM dendrimer to enhance the cellular uptake of DNA vaccine.  The permeability value assay through artificial membranes reveals that TAT-conjugated PAMAM has more capacity for transdermal delivery of the DNA compared to unmodified PAMAM dendrimer (P<0.05). CONCLUSIONS: The findings of this study suggest that TAT-conjugated PAMAM dendrimer is a promising non-viral vector for transdermal use. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.